2020
DOI: 10.3390/pathogens9060491
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Ecological Adaptation of Aedes aegypti and Aedes albopictus and Stegomyia Indices Highlight the Potential Risk of Arbovirus Transmission in Yaoundé, the Capital City of Cameroon

Abstract: The dynamic of arbovirus vectors such as Aedes aegypti and Ae. albopictus remains poorly understood in large cities in central Africa. Here, we compared the larval ecology, geographical distribution and degree of infestation of Ae. aegypti and Ae. albopictus in Yaoundé, the capital city of Cameroon, and estimated their Stegomyia indices revealing a significant potential risk of arbovirus transmission. An entomological survey was conducted in April–May 2018 in a cluster of houses randomly selected. Each selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
4
15
0
3
Order By: Relevance
“…aegypti is now mostly found in rural settings. Our findings are in accordance with previous studies in the city of Yaoundé and in Cameroon [ 37 , 41 , 54 , 55 ]. However, although in Brazil, Ae.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…aegypti is now mostly found in rural settings. Our findings are in accordance with previous studies in the city of Yaoundé and in Cameroon [ 37 , 41 , 54 , 55 ]. However, although in Brazil, Ae.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, Aedes species frequently colonize breeding and resting-habitats close to human dwellings. The high Stegomyia indexes observed in this study could result from the close proximity of both species to human dwellings as recently reported in the city of Yaoundé [55].…”
Section: Discussionsupporting
confidence: 83%
“…A great number of studies have reported strong associations between the abundance of Aedes mosquitoes and their larval habitats and poorly managed disposables as well as decorative containers [ 49 51 ]. These materials can hold water and organic debris for long periods, providing relatively stable micro-environmental and microclimatic conditions for proliferation of diverse mosquito species [ 24 , 25 , 51 , 52 ]. We also found high productivity of Aedes mosquitoes, particularly Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, estos índices han resultado muy poco eficientes en esta tarea, pues no todas las larvas o pupas sobreviven a adultos y no todas emergen a hembras de mosquito, que son las únicas transmisoras. En esta última década, los índices de adultos que cuantifican el número de mosquitos adultos por espacio físico sean por vivienda, barrio o zona geográfica determinada, han demostrado ser mejores herramientas para predecir el riesgo de transmisión [16]. Para la captura de los adultos del Ae.…”
Section: Los Vectores Del Dengueunclassified